Fast Dissolving Tablets: A Comprehensive Overview of Formulation and Manufacturing - Mangal , Ritu; Bansal , Mayank; ., Vikas (Journal of Biomedical and Pharmaceutical Research, 2024)
Despite a number of drawbacks, the oral drug delivery system is still the recommended method of medication delivery since it is easier to administer and improves patient compliance. By creating "fast dissolving tablets" (FDTs), which dissolve or disintegrate quickly without water in the mouth in a matter of seconds because of the action of a superdisintegrants or by optimising the pore structure in the formulation. Fast Dissolving Tablets (FDTs) represent an innovative drug delivery system. This article provides a comprehensive review of FDTs, covering different components used in the formulation, manufacturing technologies along with their advantages, limitations and clinical applications. Key words: fast dissolving tablets, superdisintegrants, oral drug delivery system, manufacturing technologies.